(untitled) (Cadernos de Psicologia Social do Trabalho, 2012)
Life narratives of an alcoholic military man, patient of an outpatient unit specialized in chemical dependency from the Brazilian Navy, provided an understanding on aspects which contributed to the construction of his addiction. The interviews revealed the participation of sociocultural processes that influenced his way of drinking, above all in the work environment, represented by two central categories: the "cooked crab" uniform (orange colored) and the "branquinha" (sugar cane brandy), related to the military naval professional and to alcohol consumption. Data analysis revealed how he attributed a meaning to his illness and healing process, as well as his representations of himself, with regard to the path of his involvement with alcohol and labor. Significant analytical generalizations were produced, suggesting that the experiences of a single military man can help understanding the situation of other military men, questioning the role of this institution in the construction of alcoholism.